(untitled) (Revista de História Regional, 2007)
This work searches for the so explored enslaved African universe that served as manual work in the empire, and, more specifically, in the XIX century in Rio de Janeiro. History has been showing, through oral and written sources, that there was undoubtedly some resistance to slavery. Our proposal is archeolo-gically try to identify strategies of that resistance, raising the importance of the study or the symbols created and dynamized by the slave contingent. Conside-ring that this contingent was formed by a great variety of different ethinic groups that were joined here, we tried to notice how ethic aspects were kept and the consequent restitution of the feeling of identify. In order to do that, we consider that archaelogical vestiges, directly related to the slaves, can give a new contri-bution. In this case, our analysis concentrated on ceramic pipes found at histori-cal archaeological sites of that period.